PREDICTING THE FUTURE DISTRIBUTIONS OF ENDEMIC RATTAN CALAMUS JAVENSIS BLUME UNDER CLIMATE CHANGE SCENARIOS CMIP 5 RCP 8.5 IN 2050 AND 2070 IN WEST JAVA: Predicting the future distributions of endemic rattan - Andri Wibowo; Suyud Warno Utomo (SEAMEO BIOTROP, 2025)
HIGHLIGHTSInformation on how climate change can shape Calamus javensis distributions is still lackingThe study used SDM with RCP 8.5 scenario for the years 2050 and 2070Suitable habitats for C. javensis are expected to decline by approximately 46.34%Suitable habitats for C. javensis are expected to be concentrated in western parts of West Java ABSTRACTC. javensis is an endemic rattan plant in West Java. While the information on how climate change can shape C. javensis distributions and how C. javensis can cope climate change conditions is still lacking. This information is required considering that C. javensis is an endemic plant in West Java. Then, the purpose of this study is to model the climate change impact on future C. javensis distributions. The study using species distribution modeling (SDM) covering nine locations across West Java with RCP 8.5 climate change scenario for year 2050 and 2070. The result show under the scenarios of climate change, the only appropriate habitats for C. javensis were concentrated in western parts of West Java. Within time series and climate change scenarios, the suitable habitats categorized as very high suitable for C. javensis were estimated to decline. From 2050 to 2070, suitable habitats for C. javensis will decline by around 46.34% from 1025 to 550 km2 in 2070.